IMPLEMENTATION OF PROJECT BASED LEARNING IN THE LIFE SKILL PROGRAM AT HOMESCHOOLING TAMAN SEKAR BANDUNG - Hanifa, Nadya Nida; Hatimah, Ihat; Pramudia, Joni Rahmat (Indonesian Journal of Adult and Community Education, 2022)
Project-based learning is one of the lessons that can direct students in solving problems, collaborating, and creating a creative work. This study aims to determine the implementation of project-based learning, the results of the application of project-based learning, and the inhibiting and supporting factors for the application of project-based learning at Taman Sekar Homeschooling Bandung. This research uses descriptive method and qualitative approach. The data collection techniques used were interviews, observations and documentation studies. The subjects of this research amounted to five people, namely three students, one tutor, and one person in charge of activities. Based on the research findings, it was found that 1) the implementation of project-based learning consists of six steps, namely fundamental questions, designing product planning, preparing schedules, monitoring students and project progress, assessing results and evaluating experiences. 2) The results of the application of project-based learning can be seen with an increase in cognitive, affective and psychomotor learning outcomes. 3) The supporting factor of project-based learning is the high motivation and interest of students, and the inhibiting factor is the ability of tutors who on average do not have expertise in certain fields, so the institution must bring in resource persons every project-based learning lesson